Acute Myocardial Infarction Due to Coronary Artery Dissection in the Postpartum Period - Hind N. Moussa; Malahat Movahedian; Mateo G. Leon; Baha M. Sibai (Thieme Medical Publishers, Inc., 2015)
Abstract Background Though rare, myocardial infarction secondary to coronary artery dissection is a life-threatening event. In reproductive age women, it commonly occurs during pregnancy or the postpartum period. Case We present a case of pregnancy-related acute myocardial infarction due to spontaneous coronary artery dissection in a 37-year-old woman who presented to the emergency room with shortness of breath and sudden onset of retrosternal chest pain 8 days after delivery of premature twins. Coronary artery catheterization showed 75 to 90% stenosis in the left main coronary artery (LMCA), extending into the proximal and mid left anterior descending (LAD) branch. The LMCA appearance in the heart catheterization was consistent with vasospasm, but it was not responsive to medical management. Subsequently, she underwent a second coronary artery catheterization and was found to have dissection requiring emergent coronary artery bypass graft × 3 in the LMCA, circumflex, and LAD that was followed by an uneventful recovery. Conclusion Early diagnosis and management of myocardial infarction due to coronary artery dissection in the peripartum period is crucial. This condition should be suspected in young reproductive age women, even in the setting of minimal risk factors. Angiography is required for diagnosis. Management should be individualized as it may include both invasive and noninvasive measures.